New Samarium Oxotellurites: Synthesis and Characteristic - Toibek, A.A.; Rustembekov, K.T.; Fomin, V.N.; Kaikenov, D.A. (Eurasian Journal of Chemistry, 2023)
We synthesized samarium oxotellurites SmMTeO4.5 (M — Mg, Ba) by the method of ceramic technology with solid-phase interaction (800–1200 °С) of Sm2O3 and TeO2 oxides with MgCO3 and BaCO3 carbonates. The compounds were characterized by X-ray and electrophysics methods. It has been established that the syn-thesized compounds crystallize in the tetragonal syngony with the following crystallographic characteristics: SmMgTeO4.5 — a = 12.226; c = 5.783 Å, V0un.cell = 864.38 Å3, Z = 4, ρxray. = 2.876, ρpycn. = (2.874±0.002) g∙cm-3; SmBaTeO4.5 — a = 12.717; с = 6.132Å, V0un.cell = 991.62Å3, Z = 4, ρxray. = 3.264, ρpycn. = (3.260±0.004) g∙cm-3; for both tellurites α = β = γ = 90°. The experimental and calculated values of 2 Th and d-sp, X-ray and pycnometric densities, as well as theoretical and experimental values of unit cell volumes are agreed satisfac-torily. Thus, we can confirm correctness and reliability of the results of indexing X-ray patterns of new sa-marium oxotellurites. We found that increase in the ionic radii from Mg to Ba increases the lattice parameters of the synthesized oxotellurites. Oxotellurites are crystallized in the structural types of distorted perovskite Pm3m. Based on the given study samarium oxotellurites can have semiconductor and ferroelectric properties.
Keywords: samarium oxotellurites; synthesis; crystallographic characteristics of the compounds; permittivity